GENERAL CONSIDERATIONS ON THE PENEIDS OF NORTH AND NORTHEAST OF BRAZIL - Fausto Filho, José (Arquivos de Ciências do Mar, 2018)
The study of the sistematics, distribution, ecology and fishery of peneids along the Atlantic coast of South America has increased since 1960 . However, with reference to the North and Northeast coast of Brazil, the bibliography is somewhat reduced.